Kendala-Kendala Mahasiswa Prodi Pendidikan Sejarah STKIP PGRI Sumatera Barat Dalam Melaksanakan Program Pengalaman Lapangan Kependidikan (PPLK) Periode JuliâDesember 2013 Di SMP Swasta Kota Padang - Fani, Fauziah; Nazmi, Ranti; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
The background of this study is to determine the constraints faced by students in the History of Education Program in schools implementing PPLK exercise. This study aims to gain an overview of the constraints History Education Program students in performing PPLK as it is. This type of research is a descriptive study with a qualitative approach. Respondents in this study were students of History Education Program is implementing PPLK period from July to December 2013 in the city of Padang Private SMP. The research location is SMP Pertiwi 2 Padang, SMP Pertiwi Siteba Padang, SMP Muhammadiyah 6 Padang, SMP Taman Siswa Padang, SMP Adabiah Padang dan SMP Semen Padang. Collecting data in this study is the instrument through research by distributing a questionnaire to students PPLK and interviews with officials in the teacher training school. Then the data is processed by an interactive analysis techniques. From the research findings that students PPLK find internal constraints such as: (1) constraints in planning teaching (RPP) is difficult to understand the steps to make the right lesson plan for lesson plans based on the curriculum of character, (2) constraints in the mastery of teaching materials is less IPS integrated understanding of the material, (3) constraints in the selection of instructional methods chosen method is a discrepancy with the condition of the students in the school training, (4) constraint in the selection of instructional media or the media is still a lack of infrastructure to support the PBM in school training, (5) constraints in classroom management is generally unruly students and chide when PBM. Later it was found also external constraints such as the lack of activity, attendance and student socialization PPLK with teachers and school assemblies. From this study it can be concluded that the student suffered History Education Program with internal constraints which are generally caused by a lack of understanding student learning in preparing the device, while the external constraints caused by a lack of ability PPLK students in adjusting to the school environment